A vesicular stomatitis virus-based African swine fever vaccine prototype effectively induced robust immune responses in mice following a single-dose immunization - Ma, Yunyun; Shao, Junjun; Liu, Wei; Gao, Shandian; Peng, Decai; Miao, Chun; Yang, Sicheng; Hou, Zhuo; Zhou, Guangqing; Qi, Xuefeng; Chang, Huiyun (Frontiers in Microbiology, 2024)
Introduction African swine fever (ASF) is a highly contagious hemorrhagic fever disease in pigs caused by African swine fever virus (ASFV). It is very difficult to control and prevent ASF outbreaks due to the absence of safe and effective vaccines. Methods In order to develop a safe and effective ASF vaccine for the control and prevention of ASF, two ASFV recombinant vesicular stomatitis virus (VSV) live vector vaccine prototypes, containing the gene of p72, and a chimera of p30 and p54, were developed based on the replication-competent VSV, and named VSV-p72 and VSV-p35. The immune potency of VSV-p72 or VSV-p35 alone and in combination was evaluated in BALB/c mice via intramuscular and intranasal vaccination. Results The results indicated that whether administered alone or in combination, the two vaccine prototypes showed acceptable safety in mice and, more importantly, induced high-level specific antibodies against p72, p30, and p54 of ASFV and a strong cellular immune response 28 days after vaccination. The sera from mice vaccinated with the vaccine prototypes significantly inhibited ASFV from infecting porcine alveolar macrophages (PAMs) in vitro. Most notably, the immunized sera from a mixture of VSV-p35 and VSV-p72 inhibited ASFV from infecting PAMs, with an inhibition rate of up to 78.58%. Conclusion Overall, our findings suggest that ASFV recombinant VSV live vector vaccine prototypes may become a promising candidate vaccine for the control and prevention of ASF.